Complexidade e algoritmos de jogos de blocos - Ramos, André Castro (2014)
The electronic game concept refers to reserved entertainment to spare time , but in addition to a billion dollar industry , is also potential source of several research topics , both directed to their respective areas of interest as own gaming industry . In this context, in recent decades, work has been done to deal with this type of product based on for problems to be addressed by the theory of algorithms. In this work we bring complexity results and algorithms related to three games with common characteristics , Bloxorz , On The Edge and Bobbin 3D.